COMPARATIVE CLINICAL ANALYSIS OF METAL-CERAMIC AND ALL-CERAMIC PROSTHESES - Jumayev A.A.; Olimov R.O. (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation: In prosthetic dentistry, fixed prostheses play a key role in restoring the anatomical form, masticatory function, and aesthetics of the dental arches. The most widely used types of prosthetic constructions in clinical practice remain metal-ceramic and all-ceramic prostheses. Each of these types has its own advantages and limitations, which necessitates their detailed clinical comparison.Metal-ceramic constructions have traditionally been used due to their high strength and predictability of clinical outcomes.